Search for charge-asymmetric production of W ' bosons in t(t)over-bar + jet events from pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2012)
A search is presented for charge-asymmetric production of a W ' boson that has been proposed to accommodate the forward-backward asymmetry observed in the production of top-antitop quark pairs at the Tevatron. The new heavy W ' boson would be produced in association with a top quark and would decay into top and down quarks. The data correspond to an integrated luminosity of 5.0 fb -1 in pp collisions at a center-of-mass energy of 7 TeV, recorded by the CMS detector at the LHC. No significant excess above the standard model expectations is observed, and, from a combination of the electron-plus-jets and muon-plus-jets channels, a 95% confidence level lower limit of 840 GeV/c 2 is set on the W ' boson mass for a W ' boson model with values for coupling constants to top and down quarks g L=0 and g R=2. In addition, a kinematic reconstruction of the W ' resonance mass using the inherent charge asymmetry of this model finds no indication of the presence of W ' events in the data. © 2012 CERN.